Prevalence of head and neck tumours in Calabar, South Eastern Nigeria - Kanu, Okezie Obasi; Nnoli, Martin A.; Asoegwu, Chinyere A. (Asian Journal of Medical Sciences, 2016)
Background: Malignancies in the head and neck region though relatively rare, compared to other regions of the body, they contribute significantly to morbidity and mortality in affected patients. In Nigeria, the burden of managing head and Neck malignancies is enormous and there is yet to be a unified record of nation-wide incidence of malignancies involving the head and neck region despite the fact the head and neck malignancies have been diagnosed and documented since the 1960’s. The histological pattern and frequency however seems to have some slight variation depending on the region and the identified aetiological risk factors. Aims and Objectives: The aim of this study was to determine the pattern of head and neck tumours seen in the region and the commonest malignancies in the cohort. By comparing the relative prevalence of the lesions with other centers in the country and international published literature we hope to make a case for proper tumour registry and move for nation-wide studies. Materials and Methods: The authors reviewed the histopathological data of the tumor registry at the University of Calabar Teaching Hospital, a major referral Center in South-Eastern Nigeria between 2005 and 2012. All cases of head and Neck tumours with histological diagnosis were included for analysis, their demographic data were obtained and analyzed using SPSSv16. Results: Two hundred and twenty-five specimens from the head and neck region were analyzed during this 6 year period giving an average of 34 cases per year. The Male: Female ratio was 1.2:1. The age range was from 2 years to 76 years with overall mean of 32.7 years. One hundred and forty-five cases (63.3%) were benign while 84 malignant cases (36.7%) were recorded for the study period. The average number of new malignant cases seen was 14 per year. Malignancies were commoner in those less than 50 years of age and were mostly those of epithelial origin. Conclusion: Variations in the regional demographics of head and neck tumors in the country could be accounted for by the differences in data collection methods and certain aetiological factors that may be unique to those regions. A proper tumor registry in each region, harmonized with a national cancer registry may resolve some of these discrepancies. Asian Journal of Medical Sciences Vol. 7(3) 2016 123-126